Role of Socioeconomic Factors in the Pathological Progression of Chronic Kidney Disease in Rural and Urban Settings - Abhishek Raval; Manan Jadav; Maulik Vora; Ritesh Gohil (Journal of Pharmacy and Bioallied Sciences)
Background: Chronic kidney disease (CKD) is a significant public health issue, affecting millions worldwide. The progression of CKD can be influenced by various socioeconomic factors, which may differ between rural and urban settings. This study aims to explore the role of socioeconomic factors in the pathological progression of CKD in these distinct environments. Materials and Methods: A cross-sectional study was conducted involving 500 CKD patients, with 250 from rural areas and 250 from urban areas. Data were collected through structured interviews and medical records, focusing on socioeconomic variables such as income, education, employment status, and access to healthcare services. CKD progression was assessed using estimated Glomerular Filtration Rate (eGFR) and proteinuria levels. Statistical analysis was performed using multiple regression models to identify the relationship between socioeconomic factors and CKD progression. Results: The study found significant differences in CKD progression between rural and urban settings. In rural areas, lower income (P < 0.01) and limited access to healthcare (P < 0.05) were strongly associated with accelerated CKD progression. In contrast, in urban areas, lower education levels (P < 0.01) and unemployment (P < 0.05) were the primary socioeconomic factors linked to faster CKD progression. Conclusion: Socioeconomic factors play a crucial role in the pathological progression of CKD, with distinct patterns observed in rural and urban settings. Addressing these disparities through targeted interventions and policies could improve CKD outcomes and reduce health inequalities.